2017
DOI: 10.1083/jcb.201701084
|View full text |Cite
|
Sign up to set email alerts
|

The glycolytic enzyme phosphofructokinase-1 assembles into filaments

Abstract: Phosphofructokinase-1 (PFK1) is an essential glycolysis enzyme as it catalyzes the step committing glucose to breakdown. Webb et al. show that the liver PFK1 isoform assembles into filaments in a tetramer- and substrate-dependent manner, providing insights into the spatial organization of isoform-specific glucose metabolism in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 47 publications
4
116
0
1
Order By: Relevance
“…We observed that PFK-1.1 (F674K) proteins were incapable of forming condensates upon transient hypoxia, and remained diffusely localized (Figures 7B-7C and S6E). Our findings are consistent with tetramer formation being necessary for the oligomerization of PFK (Webb et al, 2017), and provide support for multivalent interactions being necessary for the formation of PFK-1.1 condensates.…”
Section: Multivalent Interactions Underlie Pfk-11 Condensate Formationsupporting
confidence: 86%
See 3 more Smart Citations
“…We observed that PFK-1.1 (F674K) proteins were incapable of forming condensates upon transient hypoxia, and remained diffusely localized (Figures 7B-7C and S6E). Our findings are consistent with tetramer formation being necessary for the oligomerization of PFK (Webb et al, 2017), and provide support for multivalent interactions being necessary for the formation of PFK-1.1 condensates.…”
Section: Multivalent Interactions Underlie Pfk-11 Condensate Formationsupporting
confidence: 86%
“…Similar observations in mammalian tissue culture cells also demonstrated that glycolytic enzymes co-localize into clusters (Kohnhorst et al, 2017). A human isoform of phosphofructokinase (PFK) was recently shown to assemble into tetramers that oligomerize into higher-ordered filamentous structures in vitro (Webb et al, 2017). In the same study, the ability for the PFK to oligomerize in vitro was proposed to underpin its ability to dynamically compartmentalize in tissue culture cells in response to specific metabolites.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…ATP is rapidly consumed within the cytosol to fuel the remodeling of the actin cytoskeleton necessary for cell migration. 23,34 There is evidence to suggest that nutrient availability in the microenvironment can indirectly influence myeloid cell migration.…”
Section: Metabolic Regulation Of Myeloid Cell Migrationmentioning
confidence: 99%